Activation of astrocyte Gq pathway in hippocampal CA1 region attenuates anesthesia/surgery induced cognitive dysfunction in aged mice - Wang, Xupeng; Li, Yanan; Zhao, Juan; Yu, Jiaxu; Zhang, Qi; Xu, Fang; Zhang, Yahui; Zhou, Qi; Yin, Chunping; Hou, Zhiyong; Wang, Qiujun (Frontiers in Aging Neuroscience, 2022)
Postoperative cognitive dysfunction occurs mostly in the elderly, and the incidence of lower limb fracture surgery is high, which has adverse effects on the rehabilitation of elderly patients, but its mechanism is still unknown. This study observed hippocampal-dependent cognitive impairment in aged mice undergoing anesthesia and tibial fracture surgery. We used Golgi staining and neuroelectrophysiological techniques to detect structurally and functionally impaired synaptic plasticity in hippocampal CA1 region of Postoperative cognitive dysfunction aged mice, respectively. Based on the 'third party synapse' hypothesis of astrocytes, we used glial fibrillary acidic protein to label astrocytes and found an increase in abnormal activation of astrocytes in the CA1 region of hippocampus. We hypothesize that abnormal astrocyte function is the driving force for impaired synaptic plasticity. So we used chemogenetic methods to intervene astrocytes. Injection of adeno-associated virus into the CA1 region of the hippocampus bilateral to aged mice resulted in the specific expression of the Gq receptor, a receptor specially designed to be activated only by certain drugs, within astrocytes. The results of novel object recognition and conditioned fear experiments showed that CNO activation of astrocyte Gq pathway could improve the learning and memory ability and the synaptic plasticity of Postoperative cognitive dysfunction aged mice was also improved. The results of this study suggest that activation of the Gq pathway in astrocytes alleviates Postoperative cognitive dysfunction induced by anesthesia and surgery in aged mice.